Notes on Acanthoderini (Coleoptera, Cerambycidae, Lamiinae) described by Ernst Fuchs, now in the Herbert Schmid Collection, Vienna, Austria - Monné, Marcela L.; Monné, Miguel A. (Zootaxa, 2006)
A study of the species of the tribe Acanthoderini (Coleoptera, Cerambycidae, Lamiinae) described by Ernst Fuchs and deposited in the Herbert Schmid private collection is presented. Four new synonyms are established: Acanthoderes (Psapharochrus) curvistriatus Tippmann, 1960 = Acanthoderes (Psapharochrus) griseofasciata Fuchs, 1958; Acanthoderes (Psapharochrus) minuta Fuchs, 1958 = Idiomerus difficilis Melzer, 1934; Acanthoderes (Psapharochrus) sexmaculatus Fuchs, 1961 = Acanthoderes schmithi Melzer, 1935; and Sorelia cervina Lane, 1965 = Oreodera ferruginea Fuchs, 1964. Two new combinations are proposed: Oreodera hassenteufeli (Fuchs, 1958) from Acanthoderes (Pasapharochrus) and Sorelia ferruginea (Fuchs, 1964) from Oreodera. Acanthoderes (Psapharochrus) virescens Fuchs, 1962 is transferred to the subgenus Scythropopsis Thomson, 1864. Notes on the type-material and the geographical distribution are added for each species.